Early human settlements in the southern Qinling Mountains, central China. (15th May 2017) - Sun, Xuefeng; Lu, Huayu; Wang, Shejiang; Yi, Liang; Li, Yongxiang; Bahain, Jean Jacques; Voinchet, Pierre; Hu, Xuzhi; Zeng, Lin; Zhang, Wenchao; Zhuo, Haixin
Abstract: China is a key area of early human settlement in East Asia, with numerous Paleolithic localities indicating an early Pleistocene presence of hominins in northern and southern China. Considerable research has been devoted to determining possible migration routes for hominins linking the two areas. In this paper, we report the discovery of several loess-covered Paleolithic sites in the Hanzhong and Ankang Basins along the Hanjiang River in the southern piedmont of the Qinling Mountains (QLM) in central China. A chronology is developed for these sections using a combination of detailed optically stimulated luminescence dating, magnetostratigraphic analyses, and pedostratigraphic correlation with the well-dated loess–paleosol sequence of the central Chinese Loess Plateau. The results indicate that the age of the oldest lithic assemblage at the Longgangsi locality 3 Paleolithic site in Hanzhong Basin is ∼1.20 Ma, thus making this locality as one of the oldest sites in central China. Our work also indicates that hominins occupied the Hanjiang valley at several times: ∼1.2, 0.9, ∼0.6, and ∼0.1 Ma. We propose that the Hanjiang River Valley was a probable hominin routeway through the QLM because many sites corresponding to these different phases were also discovered to the north of the QLM. Future study on the Hanjiang River Valley is important for verifying the hypothesis of an early human migration route between southern and northern China. Highlights: We found stone artifacts layers within several loess sections in the Hanzhong and Ankang Basins. The loess sections were dated by detailed magnetostratigraphic analyses. Artifact layer dated to 1.20 Ma is the oldest known hominin occupation in the region. Other hominin occupation stages were at ∼0.9 Ma, ∼0.6 Ma, and ∼0.1 Ma.